Convergence of human resources technologies and industry 5.0 - Kumar, Pawan 1980-; Kumar, Sunil; Verma, Rajesh; Dadwal, Sumesh 1973- (IGI Global, 2024)
Through a combination of rapid technological advancement and the ongoing digital revolution, the role of Human Resources (HR) in shaping organizational trajectories has seen unprecedented growth. The amalgamation of digital HR technologies and the advent of Industry 5.0 pose both exceptional opportunities and formidable challenges, especially for developing economies grappling with resource constraints and skill gaps.
Keywords: Personnel management -- Data processing